2022
DOI: 10.52768/2766-7820/2099
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of surgery after gamma knife radiosurgery for parasagittaland parafalcine meningiomas is higher than meningiomas in other locations: A 10-year institutional analysis and review of the literature

Abstract: Background: Parasagittal and Parafalcine Meningiomas (PSPF) have a higher rate of recurrence, increased risk of postoperative morbidities, and less favorable outcomes after stereotactic radiosurgery compared to other ocations. Herein, we try to find factors associated with treatment failure after radiosurgery in patients with PSPF meningiomas. Methods: We retrospectively reviewed records of 104 patients with 130 Gamma Knife® Radiosurgery (GKRS) treatments for individual meningiomas at a single institution. 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This is not a novel observation; estimates of 5-year PFS among these tumours post-GKRS range between 55% and 90%, [7,21,22] with our analysis of 64% 5-year PFS demonstrating similarly modest results. Parasagittal and falcine meningiomas have been associated with higher rate of hospitalization and need for surgical intervention post-GKRS, hypothesized to result from the proximity of such tumours to eloquent cortical regions leading to a lower threshold for treatment-related symptoms and a propensity for falcine meningiomas to harbour more aggressive genetic profiles [23]. Damen et al have demonstrated that loss of 1p36 is significantly associated with regrowth of WHO Grade 1 meningiomas after radiosurgery; however, they did not stratify their cohort based on clinical features, volume, or location.…”
Section: Outcomes Of Gkrs In Meningioma and Factors Predicting Poor O...mentioning
confidence: 99%
“…This is not a novel observation; estimates of 5-year PFS among these tumours post-GKRS range between 55% and 90%, [7,21,22] with our analysis of 64% 5-year PFS demonstrating similarly modest results. Parasagittal and falcine meningiomas have been associated with higher rate of hospitalization and need for surgical intervention post-GKRS, hypothesized to result from the proximity of such tumours to eloquent cortical regions leading to a lower threshold for treatment-related symptoms and a propensity for falcine meningiomas to harbour more aggressive genetic profiles [23]. Damen et al have demonstrated that loss of 1p36 is significantly associated with regrowth of WHO Grade 1 meningiomas after radiosurgery; however, they did not stratify their cohort based on clinical features, volume, or location.…”
Section: Outcomes Of Gkrs In Meningioma and Factors Predicting Poor O...mentioning
confidence: 99%
“…The mainstay treatment of meningiomas is microsurgical resection. The meningioma prognosis depends on tumor grade, location, and patient's age [1][2][3][4]. Chemotherapy and hormonal treatment have bad results in treating meningioma, despite meningiomas' expression of hormonal receptors; subsequently, patients having recurrence after surgical resection and radiotherapy have very limited options for treatment [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The meningioma prognosis depends on tumor grade, location, and patient's age [1][2][3][4]. Chemotherapy and hormonal treatment have bad results in treating meningioma, despite meningiomas' expression of hormonal receptors; subsequently, patients having recurrence after surgical resection and radiotherapy have very limited options for treatment [2,[5][6][7][8]. As a result, searching for other potential therapies for meningioma should be encouraged by studying the role of non-coding RNAs on tumor differentiation, growth, and proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation